2010
DOI: 10.1111/j.1751-2409.2010.01016.x
|View full text |Cite
|
Sign up to set email alerts
|

Reducing “Acceptable” Stigmatization Through Legislation

Abstract: Substantial research has focused on stigmatized groups who are widely protected from discrimination under national legislation. In the current article, however, we focus our attention on those stigmatized groups who are relatively early in their quest for civil rights. In particular, we consider gay and lesbian individuals, and heavy individuals, for whom existing research is considerable enough to allow for a review. We summarize the discrimination these individuals face on a daily basis and how this discrimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 96 publications
0
16
0
Order By: Relevance
“…More generally, recognizing the illegitimate nature of discrimination sets the stage for social change to occur: research shows that perceiving intergroup inequality to be illegitimate increases individuals' feelings of anger and their willingness to take collective action (e.g., Cronin et al, 2012;Leach, Iyer, & Pederson, 2006;Iyer et al, 2007;Iyer & Ryan, 2009; for a review see Dixon, Tropp, Durrheim, and Tredoux, 2010). In addition, our findings also provide indirect evidence for the effectiveness of AAPs and other diversity programs in influencing individual attitudes (see also Barron & Hebl, 2010). The process of conducting proactive audits as part of an AAP is likely to increase individuals' awareness of the illegitimacy of group-based differential treatment.…”
Section: Discussionmentioning
confidence: 60%
“…More generally, recognizing the illegitimate nature of discrimination sets the stage for social change to occur: research shows that perceiving intergroup inequality to be illegitimate increases individuals' feelings of anger and their willingness to take collective action (e.g., Cronin et al, 2012;Leach, Iyer, & Pederson, 2006;Iyer et al, 2007;Iyer & Ryan, 2009; for a review see Dixon, Tropp, Durrheim, and Tredoux, 2010). In addition, our findings also provide indirect evidence for the effectiveness of AAPs and other diversity programs in influencing individual attitudes (see also Barron & Hebl, 2010). The process of conducting proactive audits as part of an AAP is likely to increase individuals' awareness of the illegitimacy of group-based differential treatment.…”
Section: Discussionmentioning
confidence: 60%
“…Barron (2010), for example, found that antidiscrimination legislation promoted more positive attitudes toward homosexuality (see also Barron & Hebl, 2010). More recent work extended this research to age discrimination and demonstrated that awareness of legislation protecting older workers predicted more favorable outcomes for those workers; likewise, awareness of court decisions reducing those protections (i.e., Gross v. FBL Financial Services, Inc. [Biskupic, 2009]) predicted more negative attitudes toward older targets (Cox & Barron, 2012).…”
Section: Fire All the Boomers: How Generational Labeling Legitimizes mentioning
confidence: 91%
“…In fact, gay men/lesbians remain one of the few legally unprotected minority groups in the United States. That is, although several states, municipalities, and cities offer protection, there is little federal protection regulating discrimination against gay/lesbian employees (for a review, see Barron & Hebl, 2010). The challenges such individuals face in the workplace are reason enough to suggest that they may find mentoring relationships at work especially beneficial.…”
Section: Please Scroll Down For Articlementioning
confidence: 97%